Does well‐being impact individuals' risky decisions and susceptibility to cognitive bias?. (26th February 2018) - Moulang, Carly; Strydom, Maria
Abstract: This article explores the relation between individual well‐being, risky decision‐making, susceptibility to cognitive biases and investor beliefs about investing. A survey of one hundred and two individuals revealed that those with higher satisfaction with life are more prone to taking risks. In a loss frame, participants who were most likely to take a gamble had higher levels of psychological, social and overall well‐being. Lower levels of satisfaction with life were found to impact the susceptibility of the reflection effect cognitive bias. In addition to this, well‐being was found to be associated with investment beliefs, particularly those concerning diversification, the need to be alert and active, and the risk/return trade‐off.